2020
DOI: 10.1007/s00253-020-10829-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of Cinnamomum zeylanicum bark and leaf essential oils against Candida albicans and Candida auris

Abstract: Candida infections are a significant source of patient morbidity and mortality. Candida albicans is the most common pathogen causing Candida infections. Candida auris is a newly described pathogen that is associated with multi-drug-resistant candidiasis and candidaemia in humans. The antifungal effects of various essential oils and plant compounds have been demonstrated against human pathogenic fungi. In this study, the effect of cinnamon leaf and bark essential oils (CEOs) was determined against both C. albic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 50 publications
2
29
0
1
Order By: Relevance
“…We also compared the activities of phospholipase, proteinase, and hemolysin of CA SC5314 (ATCC MYA‐2876) in different treatment groups, using CA (ATCC 10231) as the positive control. [ 50,53 ] We demonstrated that all the three virulence indices were significantly reduced in FP and FP sup‐treated groups compared to those in the FP med group. However, compared with the EC med group, the indices in EC and EC sup were higher (Figure 3H,I).…”
Section: Resultsmentioning
confidence: 87%
“…We also compared the activities of phospholipase, proteinase, and hemolysin of CA SC5314 (ATCC MYA‐2876) in different treatment groups, using CA (ATCC 10231) as the positive control. [ 50,53 ] We demonstrated that all the three virulence indices were significantly reduced in FP and FP sup‐treated groups compared to those in the FP med group. However, compared with the EC med group, the indices in EC and EC sup were higher (Figure 3H,I).…”
Section: Resultsmentioning
confidence: 87%
“…cassia bark extract. In addition, in other species of Cinnamomum , ( E )-cinnamaldehyde is also a major component, and accounted for about 66.43% of Cinnamomum zeylanicum bark essential oil [ 31 ]. In the present study, the percent content of ( E )-cinnamaldehyde in the essential oil (89.95%) was higher than in the extract (50.79%).…”
Section: Resultsmentioning
confidence: 99%
“…Bark and leaf essential oils from Cinnamomum zeylanicum proved in vitro antifungal activity against C. auris , by damaging the membrane and blocking the hyphae formation. From a chemical point of view, the main components of C. zeylanicum leaf is eugenol (62%) and C. zeylanicum bark is trans -cinnamaldehyde (66%), the other components being present at less than 7% [ 136 ].…”
Section: Traditional Medicines and Natural Compoundsmentioning
confidence: 99%